A coal-based solid waste geopolymer and its preparation method and application
Through the alkali excitation technology of coal-based solid waste polymers, high-performance polymers for power transmission and transformation projects were prepared, which solved the problems of low utilization efficiency and construction efficiency of coal-based solid waste, and realized the resources of coal-based solid waste Reuse and construction efficiency improvement.
Patent Information
- Application Number
- CN202310236754.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-13
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-03-13
AI Technical Summary
The existing technology cannot effectively utilize coal-based solid waste, resulting in low utilization efficiency, and difficult to control the construction quality in power transmission and transformation projects, complicated processes and low engineering efficiency.
Coal-based solid waste land polymer is used to prepare high-performance polymers through alkali excitation technology, which is used to manufacture prefabricated bases of terminal boxes to realize the resource utilization of coal-based solid waste, combining sodium water glass, sodium hydroxide and nitrogen Water reducing agent and other raw materials are used to prepare low-carbon and high-strength polymers, and are used for prefabricated terminal boxes for power transmission and transformation projects.
It improves the utilization rate of coal-based solid waste, reduces preparation and installation costs, improves construction efficiency, and has excellent mechanical properties, making it suitable for large-scale industrial production.
Smart Images

Figure CN116282998B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of concrete materials, and specifically relates to a coal-based solid waste geopolymer and a preparation method and application thereof. Background Art
[0002] my country is the world's largest coal producer and consumer. With the mining, processing and utilization of coal, a large amount of coal-based solid waste, such as fly ash, is generated. Pulverized coal furnace (PC) fly ash is an industrial solid waste discharged during the combustion process of coal-fired power plant boilers. The non-combustibles in the pulverized coal are partially melted due to the high temperature. At the same time, due to the effect of its surface tension, a large number of fine spherical particles are formed. During the flue gas emission process, due to the decrease in temperature, a part of the molten fine particles are rapidly cooled and become vitreous. These vitreous bodies have high potential activity; Circulating fluidized bed boiler (CFB) is a low-temperature clean coal-burning technology that uses low-calorific value and low-quality coal. The fly ash emission of circulating fluidized bed boilers is about 50% higher under the same amount of coal combustion. Untreated CFB fly ash particles are rough, loose and porous on the surface, but due to high sulfur and calcium, its chemical activity is relatively high; Coal-bearing kaolin is a kaolinite rock in the coal-bearing strata. It belongs to sedimentary hard kaolin, also known as coal gangue, and is an industrial solid waste generated during coal mining. Coal-bearing metakaolin is an amorphous aluminosilicate mineral formed by calcining and dehydrating coal-bearing kaolin at a temperature range of 600°C to 900°C. It has the characteristics of small particle size, high surface energy, low carbon emissions, and ultra-high volcanic ash effect.
[0003] So far, most of the coal-based solid waste is used as mineral admixtures in cement-based materials, and the usage is relatively small. In addition, the alkaline environment provided by cement is not enough to stimulate the volcanic ash activity of coal-based solid waste, and it is impossible to fully exert the potential of its volcanic ash activity, resulting in its utilization efficiency is not high enough and the overall utilization rate is low. At the same time, for major coal-fired power production areas such as Shanxi, Inner Mongolia, and Xinjiang, a large amount of coal-based solid waste cannot be effectively utilized, and the impact of large-scale accumulation on the environment is still very serious, occupying and polluting a large amount of arable land. Therefore, the development and utilization of solid waste resources based on fly ash and coal-based kaolin has significant economic, environmental and social benefits.
[0004] Geopolymer is a high-performance alkali-activated cementitious material that uses silicon-aluminum materials as the main raw materials and is obtained by stimulating the potential activity of the raw materials with alkali. Geopolymerization technology is an innovative technology that conforms to the concept of green development and has broad application prospects. Large solid wastes such as fly ash and coal-based kaolin, as glassy materials with high silicon-aluminum content, have a high degree of compatibility with geopolymerization technology, which can greatly improve the utilization rate of coal-based solid wastes. Compared with ordinary Portland cement, it has good physical and mechanical properties, low hydration heat, good volume stability, strong corrosion resistance, and simple production process. The production process does not require high-temperature calcination, low production energy consumption, and low emissions of greenhouse gases such as CO2.
[0005] In the construction of traditional power transmission and transformation projects, the terminal box foundation is generally constructed by on-site manual bricklaying or on-site concrete pouring. Due to the large differences in construction technology and personnel skill levels, the construction quality is difficult to control. In addition, on-site construction requires a large amount of work, is complex in procedures, is greatly affected by construction conditions, and has low project efficiency. Using coal-based solid waste as the main material to prepare the prefabricated foundation of the terminal box is of great positive significance to energy conservation, environmental protection, cost reduction and efficiency improvement in power transmission and transformation project construction. Summary of the invention
[0006] The present invention overcomes the shortcomings of the prior art and proposes a coal-based solid waste geopolymer and its preparation method and application. A green, low-carbon, high-strength geopolymer is prepared and used to manufacture a prefabricated foundation for a terminal box, thereby realizing resource recycling of coal-based solid waste and giving full play to the green and low-carbon characteristics of the geopolymer.
[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions.
[0008] A coal-based solid waste geopolymer comprises the following raw materials in parts by weight: 30-70 parts of PC fly ash; 30-70 parts of CFB fly ash; 30-45 parts of coal-based metakaolin; 65-72.5 parts of sodium water glass; 13-14.5 parts of sodium hydroxide; 14.3-15.95 parts of water; and 0.65-0.725 parts of naphthalene-based water reducer.
[0009] Preferably, the modulus of sodium water glass is 2.2-2.3.
[0010] Preferably, 50 parts of PC fly ash, 50 parts of CFB fly ash, 45 parts of coal-based metakaolin, 72.5 parts of water glass, 14.5 parts of sodium hydroxide, 15.95 parts of water, and 0.725 parts of naphthalene-based water reducer.
[0011] A method for preparing a coal-based solid waste geopolymer comprises the following steps:
[0012] 1) Pour sodium hydroxide into sodium water glass and stir at a stirring speed of ≤300r / min and a stirring time of ≥5min to obtain an alkaline excitation solution. Seal the container and place it for 24h;
[0013] 2) Pour the weighed Nai series water reducer into water and stir at a stirring speed of ≤300r / min and a stirring time of ≥5min until the water reducer is completely dissolved in the water;
[0014] 3) Pour the alkaline activated solution prepared in 1) and the solution prepared in 2) into a stirring pot, add PC fly ash, CFB desulfurized ash and coal-based metakaolin in this order, and stir to form a slurry.
[0015] An application of a coal-based solid waste geopolymer, wherein the coal-based solid waste geopolymer is used to manufacture a prefabricated foundation for a terminal box.
[0016] Further, the terminal box prefabricated foundation includes a bottom plate, a top plate, a first side plate, a second side plate and a third side plate; the left and right sides between the bottom plate and the top plate are respectively connected to the first side plate, the front side between the bottom plate and the top plate is connected to the second side plate, and the rear side between the bottom plate and the top plate is connected to the third side plate;
[0017] The left and right sides of the upper surface of the bottom plate are provided with a first socket and a through hole adapted to the first side plate, and the front and rear sides of the upper surface of the bottom plate are provided with a first socket adapted to the second side plate and the third side plate;
[0018] The front and rear sides of the lower surface of the top plate are provided with a first socket and a through hole adapted to the first side plate, and the front and rear sides of the lower surface of the top plate are provided with a second socket adapted to the second side plate surrounding the third side plate; the top plate is provided with a manhole and an equipment hole;
[0019] The first side plate includes a third socket adapted to the bottom plate and the top plate, and a fourth socket adapted to the second side plate and the third side plate.
[0020] Prestressed steel bars are provided throughout the bottom plate, the top plate and the first side plate;
[0021] The second side plate and the third side plate both include a second socket and a through hole matched with the bottom plate, the top plate and the first side plate, and a wiring channel for inlet and outlet wires.
[0022] Furthermore, sealing strips are provided at the first socket and the second socket; and threads are provided at both ends of the prestressed steel rod.
[0023] The beneficial effects of the present invention compared with the prior art are as follows:
[0024] 1. The raw materials for production are mainly coal-based solid waste, the solid waste utilization rate can reach 62.5%, and the manufacturing cost is low.
[0025] 2. Through indoor tests, the flow properties, setting time and mechanical properties of geopolymers were studied. The test results show that:
[0026] Geopolymer slurry has good flowability, which is adjustable between 140mm and 210mm, and the initial setting time and final setting time are adjustable between 1h and 9h, which can meet the preparation requirements of prefabricated foundations.
[0027] The mechanical properties of geopolymer prefabricated foundation are excellent. The early strength (3d) growth rate is much faster than that of 32.5R composite silicate cement, and the later strength (28d) is higher than that of 32.5R composite silicate cement.
[0028] 3. The prefabricated foundation of the geopolymer terminal box consists of few components and can be mass-produced through standardized templates. The prefabricated foundation can be firmly connected by bolts. It is easy to install and has good sealing performance, which can greatly improve the construction efficiency of power transmission and transformation projects.
[0029] 4. The present invention is based on bulk coal-based solid waste PC fly ash, CFB fly ash and coal-based kaolin, and obtains a new type of green terminal box prefabricated foundation with high solid waste utilization rate through strong alkaline excitation under normal temperature and pressure conditions. At the same time, it has good mechanical properties and simple preparation and installation processes, and can realize standardized industrial production. It has great positive significance for the comprehensive and resource utilization of coal-based solid waste and the cost reduction and efficiency improvement of power transmission and transformation engineering construction. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a flow chart for preparing coal-based solid waste geopolymers from Examples 1-4;
[0031] Figure 2 This is an overall schematic diagram of Example 5;
[0032] Figure 3 This is a schematic diagram of the bottom plate of Example 5;
[0033] Figure 4 This is a schematic diagram of the top plate of Example 5;
[0034] Figure 5 This is a schematic diagram of a first side panel of Embodiment 5;
[0035] Figure 6 This is a schematic diagram of the second side panel of Example 5;
[0036] Figure 7 This is a schematic diagram of the third side panel of Example 5. DETAILED DESCRIPTION
[0037] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer, the present invention is further described in detail in conjunction with the embodiments and the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The technical solutions of the present invention are described in detail below in conjunction with the embodiments and the accompanying drawings, but the scope of protection is not limited thereto.
[0038] Example 1
[0039] A coal-based solid waste geopolymer, wherein the raw materials for preparing the geopolymer are: 30 parts of PC fly ash, 70 parts of CFB fly ash, 30 parts of coal-based metakaolin, 65 parts of water glass, 13 parts of sodium hydroxide, 14.3 parts of water, and 0.65 parts of naphthalene-based water reducer.
[0040] Example 2
[0041] A coal-based solid waste geopolymer, wherein the raw materials for preparing the geopolymer are: 50 parts of PC fly ash, 50 parts of CFB fly ash, 30 parts of coal-based metakaolin, 65 parts of water glass, 13 parts of sodium hydroxide, 14.3 parts of water, and 0.65 parts of naphthalene-based water reducer.
[0042] Example 3
[0043] A coal-based solid waste geopolymer, wherein the raw materials for preparing the geopolymer are: 70 parts of PC fly ash, 30 parts of CFB fly ash, 30 parts of coal-based metakaolin, 65 parts of water glass, 13 parts of sodium hydroxide, 14.3 parts of water, and 0.65 parts of naphthalene-based water reducer.
[0044] Example 4
[0045] A coal-based solid waste geopolymer, wherein the raw materials for preparing the geopolymer are: 50 parts of PC fly ash, 50 parts of CFB fly ash, 45 parts of coal-based metakaolin, 72.5 parts of water glass, 14.5 parts of sodium hydroxide, 15.95 parts of water, and 0.725 parts of naphthalene-based water reducer.
[0046] The chemical compositions of PC fly ash, CFB fly ash and coal-based metakaolin used in Examples 1-4 are shown in Table 1; water glass is commercially available industrial water glass (SiO2 content 29.20%, Na2O content 12.90%, modulus 2.26, Baume degree 50); sodium hydroxide is commercially available analytical grade sodium hydroxide with a purity of more than 99%; city tap water is used for the test water; the water-cement ratio is 0.4; and the mold is a 40 mm × 40 mm × 160 mm cement mortar triple mold.
[0047]
[0048] The preparation method of the coal-based solid waste geopolymer described in Examples 1-4 is:
[0049] (1) Pour 100 parts by weight of analytically pure sodium hydroxide into 2.2 modulus sodium water glass at a stirring speed not exceeding 300 r / min for at least 5 minutes until the analytically pure sodium hydroxide is completely dissolved in water to obtain an alkaline excitation solution. Seal the container and place it for 24 hours.
[0050] (2) Weigh the casting materials of prefabricated components according to their weight.
[0051] (3) Pour the weighed naphthalene-based water reducer into water and stir at a stirring speed not exceeding 300 r / min for at least 5 minutes until the water reducer is completely dissolved in the water.
[0052] (4) Pour the alkaline activated solution prepared in (1) and the solution prepared in (3) into a stirring pot, and add the PC fly ash, CFB desulfurized ash and coal-based metakaolin in this order.
[0053] (5) Place the pot on a fixed stand, raise it to a fixed position, start the machine, stir at a low speed for 30 seconds, use a scraper to scrape the slurry on the blades and the pot wall into the pot, then turn at a high speed for 30 seconds, stop for 60 seconds, and stir at a high speed for another 60 seconds to make a slurry.
[0054] Analysis of test results:
[0055] The flow properties and coagulation time of the coal-based solid waste geopolymers prepared in Examples 1-4 are shown in Table 2:
[0056]
[0057] The mechanical properties of the coal-based solid waste geopolymers prepared in Examples 1-4 are shown in Table 3:
[0058]
[0059] Most of the PC fly ash selected in this embodiment is glass microspheres, which are spherical particles with smooth surface, have morphological effects, can generate water-reducing potential energy, play the role of ball bearings, reduce the water demand of geopolymers, and improve their fluidity; in addition, the CFB desulfurization ash and coal-based kaolin selected in the experiment are both highly active solid wastes with a large content of amorphous aluminosilicate substances formed at high temperatures. In a strong alkaline environment, the Si-O and Al-O bonds therein are easily broken to form a series of [SiO4] and [AlO4] monomers, and then these geopolymeric [SiO4] and [AlO4] monomers act as network formers to undergo dehydration and polymerization to form a Si-O-Al three-dimensional network structure, wherein the CaO in the CFB fly ash can be used as a network regulator to optimize the network structure and facilitate the formation of higher strength.
[0060] Example 5
[0061] The coal-based solid waste geopolymer obtained in Example 2 is used to prepare a prefabricated foundation of a terminal box made of coal-based solid waste for power transmission and transformation engineering, and the specific steps are as follows:
[0062] (1) Pour the prepared coal-based solid waste geopolymer slurry into the corresponding mold in two layers. When placing the first layer, place it about 2 / 3 of the tank height, then vibrate it on a vibration table for 60 seconds. Then place the second layer and vibrate it for another 60 seconds.
[0063] (2) Remove the test mold, scrape off the part that exceeds the test mold with a scraper, and smooth the surface of the test mold.
[0064] (3) Remove the slurry remaining around the test mold, mark the slurry specimen number on the test mold, and immediately place the marked test mold into the curing room.
[0065] (4) After being cured in the curing room for 24 hours, the slurry specimens are taken out, demoulded and marked, and then immediately placed in the curing room for curing to the specified age.
[0066] All the above steps are carried out under normal pressure.
[0067] The structure of the obtained prefabricated foundation of the terminal box specifically includes a bottom plate 1 , a top plate 2 , a first side plate 3 , a second side plate 4 and a third side plate 5 .
[0068] The bottom plate 1 includes a first socket 6 and a through hole 7 located on the upper surface and adapted to the first side plate 3 , a first socket 8 adapted to the second side plate 4 and the third side plate 5 , and a prestressed steel rod 9 passing through the bottom plate 1 .
[0069] The top plate 2 includes a first socket 6 and a through hole 7 located on the lower surface, which are adapted to the first side plate 3, a second socket 10 adapted to the second side plate 4 and the third side plate 5, a prestressed steel rod 9 passing through the bottom plate 2, and a manhole 11 and an equipment hole 12 located on the upper surface. The first socket 6 and the through hole 7 are consistent in size and position with those in the bottom plate 1.
[0070] The first side panel 3 includes a third socket 13 adapted to the bottom panel 1 and the top panel 2 and a fourth socket 16 adapted to the second side panel 4 and the third side panel 5 , including a first through-length prestressed steel rod 14 and a second through-length prestressed steel rod 15 adapted to the bottom panel 1 and the top panel 2 .
[0071] The second side plate 4 includes a second socket 17 and a through hole 7 adapted to the bottom plate 1, the top plate 2 and the first side plate 3, and a wiring channel 18 for incoming and outgoing wires.
[0072] The underground portion of the third side plate 5 is consistent with the second side plate 4, and the above-ground portion thereof is a solid whole.
[0073] The first socket 6 and the second socket 17 are both provided with sealing strips, and both ends of the prestressed steel rod 9 and the first through-length prestressed steel rod 14 and the second through-length prestressed steel rod 15 are threaded so as to be connected using a nut 19 .
[0074] The prefabricated foundation bottom plate 1, the first side plate 3 and the second side plate 4 of the terminal box are located underground, the top plate 2 and the third side plate 5 are flush with the ground with the upper surface of the top plate 2 as a reference, the upper part is paved with hard ground, and the rest is located on the ground.
[0075] A method for installing the above-mentioned terminal box prefabricated foundation comprises the following steps:
[0076] (1) Excavate the foundation pit to a depth consistent with the height of the precast foundation;
[0077] (2) Suspend the first side plate 3, align the third socket 13 with the first socket 6 of the bottom plate 1, ensure that all the first full-length prestressed steel rods 14 and the second full-length prestressed steel rods 15 are inserted from the reserved through holes 7 of the bottom plate, and connect the first side plate 3 and the bottom plate 1 through the end threads and nuts 19;
[0078] (3) Place the installed base plate 1 and first side plate 3 into the bottom of the foundation pit;
[0079] (4) Suspending the top plate 2, aligning the first socket 6 of the top plate 2 with the third socket 13 of the first side plate 3, inserting all the first full-length prestressed steel rods 14 and the second full-length prestressed steel rods 15 of the first side plate 3 into the reserved through holes 7 of the top plate 2, and connecting the top plate 2 and the first side plate 3 through the end threads and nuts 19 to form a cylindrical structure;
[0080] (5) Suspend the second side plate 4 and the third side plate 5, align their second sockets 17 with the first sockets 8, the second sockets 10 and the fourth sockets 16 of the cylindrical structure, insert all the prestressed steel bars 9 of the cylindrical structure into the reserved through holes 7 of the second side plate 4 and the third side plate 5, connect the second side plate 4 and the third side plate 5 to the cylindrical structure through the end threads and nuts 19, and complete the installation of the prefabricated foundation.
[0081] The above content is a further detailed description of the present invention in combination with a specific preferred embodiment. It cannot be determined that the specific embodiments of the present invention are limited to this. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the present invention, which should be regarded as belonging to the present invention and the scope of patent protection determined by the submitted claims.
Claims
1. A coal-based solid waste geopolymer, characterized in that: The preparation method is composed of the following raw materials in parts by weight: 50 parts of PC fly ash, 50 parts of CFB fly ash, 45 parts of coal-based metakaolin, 72.5 parts of sodium water glass, 14.5 parts of sodium hydroxide, 15.95 parts of water, and 0.725 parts of naphthalene-based water reducer; The chemical compositions of PC fly ash, CFB fly ash and coal-based metakaolin are: PC fly ash contains 49.34% SiO2, 35.78% Al2O3, 3.08% CaO, 0.41% MgO, 4.90% Fe2O3, 1.21% SO3, 1.63% K2O, 0.49% Na2O, 1.99% TiO2, and 1.17% other impurities; CFB fly ash contains 25.54% SiO2, 19.95% Al2O3, 25.09% CaO, 0.69% MgO, 5.94% Fe2O3, 11.86% SO3, 0.44% K2O, 0.21% Na2O, 1.35% TiO2, and 8.93% other impurities; Coal-bearing metakaolin contains 52.62% SiO2, 45.42% Al2O3, 0.17% CaO, 0.11% MgO, 0.45% Fe2O3, 0.13% K2O, 0.25% Na2O, and 0.85% TiO2; The method for preparing the coal-based solid waste geopolymer comprises the following steps: 1) Pour sodium hydroxide into sodium water glass and stir at a stirring speed of ≤300r / min and a stirring time of ≥5min to obtain an alkaline excitation solution. Seal the container and place it for 24h; 2) Pour the weighed naphthalene-based water reducer into water and stir at a stirring speed of ≤300r / min and a stirring time of ≥5min until the water reducer is completely dissolved in the water; 3) Pour the alkaline activated solution prepared in 1) and the solution prepared in 2) into a stirring pot, add PC fly ash, CFB desulfurized ash and coal-based metakaolin in this order, and stir to form a slurry; The coal-based solid waste geopolymer is prepared by strong alkaline excitation under normal temperature and pressure conditions and is used to manufacture a prefabricated foundation for a terminal box.